2008
DOI: 10.1037/0882-7974.23.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in visuospatial working memory.

Abstract: In two visuospatial working memory (VSWM) span experiments, older and young participants were tested under conditions of either high or low interference, using two different displays: computerized versions of a 3 ϫ 3 matrix or the standard (randomly arrayed) Corsi block task (P. M. Corsi, 1972). Older adults' VSWM estimates were increased in the low-interference, compared with the high-interference, condition, replicating findings with verbal memory span studies. Young adults showed the opposite pattern, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 51 publications
12
52
0
Order By: Relevance
“…4, the number of cells memorized increases as age increases until the age range of 21-25 years, and then decreases gradually with increasing age. This tendency of age-memory relationship is consistent with the findings of previous work [32][33][34]. The peak median in this age group is approximately 10 cells.…”
Section: Visuospatial Memory Performancesupporting
confidence: 82%
“…4, the number of cells memorized increases as age increases until the age range of 21-25 years, and then decreases gradually with increasing age. This tendency of age-memory relationship is consistent with the findings of previous work [32][33][34]. The peak median in this age group is approximately 10 cells.…”
Section: Visuospatial Memory Performancesupporting
confidence: 82%
“…It has been argued that inhibition is needed to suppress previously, but no longer, relevant items from working memory so as to minimize interference within these tasks (Friedman & Miyake, 2004;Hasher et al, 1999;Kane, Conway, Hambrick, & Engle, 2007). Furthermore, numerous studies suggest that the ability to delete previously attended information shows a marked decline with age, as older adults' performance on these tasks is greatly improved by conditions that minimize the build-up of proactive interference (e.g., Lustig, May, & Hasher, 2001;May et al, 1999;Rowe, Hasher, & Turcotte, 2008Sahakyan, Delaney, & Goodmon, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, using magnetic resonance imaging (MRI) scans, Gur et al (1991) observed that brain atrophy as indicated by increased cerebrospinal fluid volume with age was greater in males than in females; Cowell et al (1994) found greater age-related reductions in brain volume for both frontal and temporal lobes in males than in females; and Pruessner, Collins, Pruessner and Evans (2001) found a reduction in hippocampal volume across early adulthood for males but not for females. From such findings, it would be predicted that corresponding age by gender interactions would be found in behavioral data and, indeed, greater age-related cognitive decline in males than in females has been observed in both cross-sectional and longitudinal studies (e.g., Barrett-Connor & Kritz-Silverstein, 1999;Larrabee & Crook, 1993;Meyer et al, 1999;Rowe, Turcotte, & Hasher, 2004;Wiederholt et al, 1993;Zelinski & Stewart, 1998). Interestingly, similar results have been found in two studies of spatial memory in rhesus monkeys (Lacreuse et al, 2005;Lacreuse, Herndon, Killiany, Rosene, & Moss, 1999), suggesting that biological rather than sociocultural factors may underlie the gender differences in age-related decline.…”
Section: Introductionmentioning
confidence: 95%